2011
DOI: 10.4049/jimmunol.1100099
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Mediates Enhancement of HIV Replication in Astrocytes by Inducing an Antagonist of the β-Catenin Pathway (DKK1) in a STAT 3-Dependent Manner

Abstract: Typically, IFN-γ is an antiviral cytokine that inhibits the replication of many viruses, including HIV. However, in the CNS, IFN-γ induces HIV-productive replication in astrocytes. Although astrocytes in vitro are refractory to HIV replication, recent in vivo evidence demonstrated that astrocytes are infected by HIV, and their degree of infection is correlated with proximity to activated macrophages/microglia. The ability of IFN-γ to induce HIV replication in astrocytes suggests that the environmental milieu i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 42 publications
10
86
0
Order By: Relevance
“…3 and 4). This is consistent with the results of our previous study in human astroglioma cells, in which IFNγ regulates the β-catenin pathway in a STAT3-dependent manner, in which STAT1 it is not necessarily involved (21).…”
Section: A B C Dsupporting
confidence: 93%
See 3 more Smart Citations
“…3 and 4). This is consistent with the results of our previous study in human astroglioma cells, in which IFNγ regulates the β-catenin pathway in a STAT3-dependent manner, in which STAT1 it is not necessarily involved (21).…”
Section: A B C Dsupporting
confidence: 93%
“…To further identify the key signaling components for IFNγ to induce apoptosis in HepG2 cells that express excess β-catenin, we used inhibitors for STAT1, STAT3 and caspases. In a previous study, we demonstrated that STAT1 and STAT3 were induced by IFNγ in human astroglioma cells, in which STAT3 played a key role in the regulation of the β-catenin pathway (21). In the present study, we confirmed the STAT1 and STAT3 activation induced by IFNγ, and the effects of STAT1 inhibitor, FLUD, and STAT3 inhibitor, S3I, in HepG2 cells with high levels of (Fig.…”
Section: Roles Of Stats and Caspases In Ifnγ-induced Apoptosis Insupporting
confidence: 85%
See 2 more Smart Citations
“…Flow cytometry was performed as previously described (27). FITC-conjugated mouse anti-human activated STAT1 antibody was purchased from Cell Signaling, USA.…”
Section: Methodsmentioning
confidence: 99%